KAJIAN APLIKASI TEKNOLOGI INSEMINASI BUATAN DALAM UPAYA PENINGKATAN PRODUKTIVITAS DAN PENDAPATAN USAHA TERNAK SAPI POTONG DI KABUPATEN TASIKMALAYA - Suprianto Suprianto; Dedi Djuliansah (Universitas Galuh, 2016)
The aims of this research are to know: level of productivity and income of cow farmers by artificial insemination, and natural farmer; in Tasikmalaya. Survey was the method used. There were 15 farmer as sampling unit of The Insemination Farmer and 17 the natural farmer. The result of the research can be concluded that: The produkductivity of artificial insemination farmer more than the productivity of natural farmer; both of the farmers were on equal fragnant productivity. It were one baby cow for one time of the fragnan. But the artificial insemination farmer have short interval. On 23 Th months the artificial insemination farmers have two times fragnant; the growth rate of the artificial insemination cow was faster then the growth rate of the natural cow. The baby cow by artificial insemination reach 105-110 kg on 4 Th months, but the natural were only 65-75 kg on 6-8 Th months. Net income of artificial insemination farmers were 5,65 percents on the total investments, while the natural farmer were 3,44 percent per month.